Bibliotecário acadêmico: papéis atribulados pelo ritmo descompassado entre o ambiente universitário e suas bibliotecas - Julia Goncalves da Silveira (1991)
This survey aims to identify the possible barriers that interfere in the professional life of the librarians of the Federal University of Minas Gerais. Data were collected through questionnaires that reached a return rate of 88,46%. Some aspects concerning the general work conditions of these academic librarians were studied. Among these aspects are: professional training and qualification, tasks, participation in otheractivities developed within the Department, University, and provfessional associations at a regional level. and availability of financial and human rescources in the specific work places. Data analysis led to the conclusion that the main obstacles for a more convenient performance ofthese librarians are related to the following: most of them have a professional qualification restricted to a Bachelor degree in librarianship;most of them feel dissatisfied with the few opportunities provided by the institution for gaining and updating knowledge; there is no institutibnal policy that stimulates and assures a continuous improvment of librarians; the professionals have no initiative in practicing work modalities other their technical attributions; there is no planning for librarian work; there is a qualitative and quantitative deficiency in terms of human and financialresources. Recommendations and suggestions are included.